PROCESS OF TEACHING IN PHYSICAL EDUCATION AND TRAINING SCHOOL (Fiep Bulletin - online, 2014)
This text analyzes lies in relation to the processes of teaching physical education in the context of training and school. Refers to a theoretical study indicates that the main consideration synthesis: the need for dialogue with the school to overcome difficulties in production of different models of the physical education classes, converging with the pedagogical consistent within theoretical and training courses for teachers of Physical Education is essential to create conditions for future professionals understand that it is important to be aware of the problems, it is also important that it be able to propose alternatives to Brazilian society.
Keywords: Physical Education; Teaching; School